Crystal Orientation Evolution During Friction Stir Welding of 6082 Aluminum Alloys - ZHANG Liang-liang; WANG Xi-jing; LIU Xiao (Cailiao gongcheng, 2018)

(untitled)
The evolution of grain morphology, grain boundary characterization, misorientation distribution and texture in upper part of base metal and nugget zone during friction stir welding of 6082-T6 aluminum alloys was investigated by the electron backscattered diffraction (EBSD) technique. The results show that the grains of the base metal are refined due to the experienced plastic deformation and dynamic recrystallization; based on the Thompson tetrahedrons that are formed behind the pin, the (110)[001] Goss texture and (114)[221] texture are formed firstly in nugget zone adjacent to keyhole. Those grains rotate along 〈110〉 crystallographic direction due to the stress introduced by the shoulder, leading subsequently to the formation of the (112)[111] copper texture and (111)[112] texture; the nugget zone located at a distance of 40mm from the keyhole experiences shoulder extrusion, thus, the plastic deformation degree becomes bigger and the[110] fiber texture consequently dominates in this region.